High-performance software for designing complex Cyber-Physical Systems on the parallel computers - Klushyn, Yuriy (Lviv Politechnic Publishing House, 2018)
To study the effective functioning and behavior of parallel computing systems (which may be an integral part of the Cyber-Physical System), a high-performance software package based on mathematical models, methods and algorithms for stochastic modeling has been developed at the design stage. This software package completely solves the design problem – the parameters of a computing system have been calculated: its computational power, the average value of task execution time or various tasks on homogeneous resources of a parallel computing system, the distribution function of the task execution time. Based on the analysis of the parameters obtained, as well as indicators of the reliability of the system, the configuration of a parallel computing system has been selected or the possibility of using a previously selected computing system to perform the task has been considered.
Keywords: Cyber-Physical Systems; parallel computing systems; a set of interrelated works; multilevel stochastic modeling; Markov process; distribution function of a random variable